Sind Nichtregierungsorganisationen die besseren Entwicklungshelfer? - Peter Nunnenkamp; Rainer Thiele (Kiel Institute for the World Economy (IfW), 2009)
Non-governmental organizations (NGOs) are widely expected to provide better targeted aid than state agencies with a hidden agenda of commercial and political self-interest. However, principal-agent models question that NGOs decide autonomously on aid allocation. Indeed, we show empirically that NGO aid offers no panacea: The focus of NGOs on the neediest recipients turns out to be surprisingly weak. NGOs hardly make use of the perceived comparative advantage of working in difficult environments." Rather, they are strongly inclined to follow the herd of other NGOs and mimic the allocation behaviour of state agencies, especially if they depend on public co-financing.
Keywords: F35; 330; Nichtregierungsorganisationen; Allokation der Entwicklungshilfe; Private Entwicklungshilfe; Nichtregierungsorganisation; Entwicklungshilfe; Allokation; Agency Theory; Herdenverhalten; OECD-Staaten